Analyzing Fiscal Space Options for Health in Zimbabwe - World Bank (World Bank, Washington, DC, 2017)
The fiscal space analysis for the health sector in Zimbabwe is timely and the need for such analysis has been strongly expressed by the government and its development partners. This imperative is Justified on multiple grounds. As the country is hit by an economic crisis resulting in lower revenues and cuts in expenditures, Understanding the consequences and assessing coping strategies for the health sector is critical. As the Country engages in The implementation of its new health sector strategy which sets ambitious targets in terms of Health outcomes towards Universal Health Coverage, it Is also critical to explore ways to increase resources for the sector, Even in A constrained macro-fiscal environment. The fiscal space analysis also highlights the major sources of inefficiencies to identify areas for improvement to increase the value for money in the sector. Overall, the fiscal space analysis aims to generate evidence to inform MOFED and MOHCC on short-term and medium-term options to generate resources for the health sector. It will provide evidence for government partner consultations on short-term options and choices in light of declining public financing for health and a difficult economic growth outlook.